Efeito antiinflamatório da atorvastatina na periodontite induzida por ligadura em ratos - Pinheiro, Paula Goes (2009)
Periodontitis is a disease characterized by leukocyte influx, loss of connective tissue and bone resorption. Statins are drugs widely used to hyperlidemia treatment, in which stand out Atorvastatin (ATV) due to its important pleiotropic effects, such as antiinflammatory activity and anabolic bone capacity, with great potential to modify chronic inflammatory disease course. In this way the aim of this work was to evaluate the aniinflammatory effect of ATV, through ligature-induced periodontitis model in rats. Wistar male, located in experimental groups: control (0.9% Saline), and 5 subgroups (ATV 0.3, 1, 3, 9 or 27 mg/kg), given orally daily, 30 min before nylon thread 3.0 aroud cervix of second left upper molars during 11 d, when then, rats were sacrified, and the following parameters were analyzed: 1) alveolar bone loss (ABL), evaluated through morphometric, histologic and radiographic studies; 2) Sistemic evaluation through a) leucograms performed before and after ligature (6h and 2, 7, and 11 d); b) corporal mass variation; c) of liver and kidney analysis, by serum biochemical dosage and histological study; and d) serum evaluation of Bone-Specific Alkaline Phosphatase (BALP). Animals submitted to 11 d periodontitis presented intense bone resoption. Low dose of ATV (0.3 mg/kg) was not able to prevent ABL (p>0.05), meanwhile the other dose ATV (1, 3, 9 or 27 mg/kg) were , in a significant way able to reduce ABL by 35%, 39%, 53%, 56%, respectively. Such inhibition was corroborated by histological analysis where was observed that ATV (27 mg/kg) caused greater periodontal tissue preservation [Mean 1.5 (0-2)], when compared to Saline [Mean 3 (2-3)] . In addition, animals submitted to periodontitis presented a significant reduction on periodontal radiographic density (58%). ATV (1, 3 ou 9 mg/kg) preserved such density in 5%, 9% e 20%, respectively. The leucogram of animals submitted to periodontitis presented leukocytosis peak on the 6th h mediated by neutrophils and new leukocytosis after 7th d due mononuclear cells. ATV (27 mg/kg) was able to reduce leukocytosis, decreasing neutrophils or mononuclear cells respectivelly (p<0.05), as well as, it was able to reduce initial corporal mass loss seen in periodontitis. Serum biochemical and histological analysis of liver and kidneys of animals with 11 d periodontitis treated with (ATV 27 mg/kg) or not (Saline), did not show alterations (p>0.05). It was observed a raise on serum BALP dosage variation of animals with 11 d periodontitis (Saline: 63.4±10.8 U/l), while ATV (27 mg/kg) prevented that increase (13.6±3.5 U/l) (p<0.05).In this way, the results demonstrated that this periodontitis model in rats reproduced the main aspects of periodontal disease in humans, and ATV reduced periodontal destruction, without cause significant alterations on liver and kidneys, besides of keeping BALP activitys, what suggests that ATV may be an important pharmacological approach as an adjuvant to periodontal therapy, to be evaluated clinically, due to its efficacy and safety.